The Impact of Transformational Leadership on Employee Performance: Mediating Roles Of Employee Engagement and Job Satisfaction - Yaseen, Muhammad (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
The hotel industry in Pakistan encounters continuous challenges, such as elevated personnel turnover, variable service quality, and diminishing engagement levels, which impede its growth potential despite its substantial contribution to the national GDP. This study investigates the influence of transformational leadership (TL) on employee performance (EP) and job satisfaction (JS), highlighting the mediating effect of employee engagement (EE) via a dual mediation model.A quantitative cross-sectional design was employed, collecting data 151 employees from hotels and resorts in Pakistan by stratified random sampling. Data was gathered using structured questionnaires that incorporated validated instruments, such as the Multifactor Leadership Questionnaire (MLQ), the Utrecht Work Engagement Scale (UWES), and adapted measures for work satisfaction and employee performance. Data analysis was conducted using SPSS and AMOS, employing descriptive statistics, reliability assessments, correlation analysis, and structural equation modeling (SEM) to investigate both direct and indirect impacts.The findings validated that transformative leadership positively affects employee engagement and job satisfaction, hence improving employee performance. The dual mediating role of engagement and satisfaction underscores the psychological mechanisms by which leadership enhances employee outcomes in the hospitality industry.The results indicate that hotel managers ought to develop transformational leadership behaviors to strategically enhance staff engagement and happiness, consequently improving service quality and operational performance. This study enhances the leadership literature by offering empirical insights into the psychological mechanisms that mediate the impact of transformative leadership on employee outcomes, particularly within a non-Western hospitality context.